A reconfigurable mechanism model for error identification in the double ball bar tests of machine tools. (June 2021) - Wang, Zhi; Wang, Delun; Yu, Shudong; Li, Xiaopeng; Dong, Huimin
Abstract: A unified approach is presented in this paper for error identification of machine tools by means of double ball bar (DBB) tests and a reconfigurable mechanism model. The mechanism model consists of a kinematic chain describing motion of the tested object and a spherical-prismatic-spherical (SPS) chain describing motion of the DBB. Depending on the types of motion of a machine tool measured, five different mechanisms, designated as PP-SPS, PPP-SPS, R–SPS, RR-SPS, and PPRRR-SPS, are employed to deal with (i) two linear axes, (ii) three linear axes, (iii) one rotary axis, (iv) two rotary axes, and (v) three linear and two rotary axes, respectively. Treating the whole DBB test loop as a mechanism allows for the measured data of the DBB, the structure parameters of the mechanism and the motion parameters to be coupled together by the displacement equations. The structure parameters are obtained using the measurements with the help of kinematic synthesis of mechanisms and saddle point programming. The position-independent geometric errors and the mounting position of the DBB, and the error motions caused by the position-dependent geometric errors of the machine tool are also discerned successfully with the proposed mechanism concept for any DBB mounting position and direction. The experimental results confirm that the proposed mechanism approach is valid for error identification of machine tools composed of the linear and rotary axes. Graphical abstract: Image 1 Highlights: A series of reconfigurable mechanism models for the DBB tests are presented. The mechanism models can be used to constitute new models for different DBB tests. The position-independent geometric errors are identified absolutely by one test. The measured data of the DBB caused by different geometric errors are clarified. The identification results are independent of the mounting position of the DBB.